2021
DOI: 10.3389/fcell.2021.654654
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Nanotube Modified With Silver Cross-Linked Basic Fibroblast Growth Factor Improves Osteoblastic Activities of Dental Pulp Stem Cells and Antibacterial Effect

Abstract: Titanium modifications with different silver loading methods demonstrate excellent antibacterial properties. Yet pure silver nanoparticles with limited bioactive properties may delay regeneration of bone surrounding the dental implant. Therefore, loading silver with bioactive drugs on titanium surfaces seems to be a very promising strategy. Herein, we designed a silver (Ag) step-by-step cross-linking with the basic fibroblast growth factor (bFGF) by polydopamine (PDA) and heparin on titanium nanotube (TNT) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Most previous studies focused on the development of differentiation medium to induce MSCs into cells derived from three different germ layers ( Lee et al, 2004 ; Xu et al, 2004 ; Anghileri et al, 2008 ; Pavlova et al, 2012 ; Andrzejewska et al, 2019 ; Higuchi et al, 2019 ), and these studies demonstrated that MSCs had great potential to differentiate into cells derived from all three germ layers ( Lee et al, 2004 ; Xu et al, 2004 ; Anghileri et al, 2008 ; Pavlova et al, 2012 ; Andrzejewska et al, 2019 ; Higuchi et al, 2019 ); in some ways, these characteristics are comparable to hPSCs ( Higuchi et al, 2015 ; Andrzejewska et al, 2019 ). Currently, only a few studies have investigated the effect of cell culture biomaterials on MSC differentiation into specific lineages of cells, especially neural cell lineages ( Prabhakaran et al, 2009 ; Zhang et al, 2016 ; Ghorbani et al, 2018 ; Luo et al, 2018a ; Luo et al, 2018b ; Hsiao et al, 2020 ; Luo et al, 2020 ; Albashari et al, 2021 ; Zhu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies focused on the development of differentiation medium to induce MSCs into cells derived from three different germ layers ( Lee et al, 2004 ; Xu et al, 2004 ; Anghileri et al, 2008 ; Pavlova et al, 2012 ; Andrzejewska et al, 2019 ; Higuchi et al, 2019 ), and these studies demonstrated that MSCs had great potential to differentiate into cells derived from all three germ layers ( Lee et al, 2004 ; Xu et al, 2004 ; Anghileri et al, 2008 ; Pavlova et al, 2012 ; Andrzejewska et al, 2019 ; Higuchi et al, 2019 ); in some ways, these characteristics are comparable to hPSCs ( Higuchi et al, 2015 ; Andrzejewska et al, 2019 ). Currently, only a few studies have investigated the effect of cell culture biomaterials on MSC differentiation into specific lineages of cells, especially neural cell lineages ( Prabhakaran et al, 2009 ; Zhang et al, 2016 ; Ghorbani et al, 2018 ; Luo et al, 2018a ; Luo et al, 2018b ; Hsiao et al, 2020 ; Luo et al, 2020 ; Albashari et al, 2021 ; Zhu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced osteogenic differentiation of dental pulp stem cells. Albashari et al, 2021 [ 46 ], in vitro study Titanium nanotubes hydrothermally treaded to incorporate Sr, then immersed in AgNO 3 solution. Exhibited long-lasting antibacterial effect and inhibited bacterial adhesion.…”
Section: Literature Outcomementioning
confidence: 99%
“…This increases the roughness and surface area, promoting better osseointegration; however, this creates more favourable conditions for bacterial growth ( Figure 5 ). Silver nanoparticles were added to Ti-nanotubes to prevent bacterial growth and biofilm formation [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Titanium nanotubes filled with AgNPs showed good antibacterial activity against Gram-positive and Gram-negative bacteria shown in Table 3 .…”
Section: Literature Outcomementioning
confidence: 99%
“…Ag + is an agent with broad-spectrum antimicrobial property, which can disrupt bacterial metabolism via increasing bacterial membrane permeability and inducing intracellular oxidation ( Wang G. et al, 2017 ). Through direct immersion in silver nitrate solution and subsequent reduction to Ag under ultraviolet irradiation, and thus Ag nanoparticles can be directly decorated on PDA-modified substrates ( Tejido-Rastrilla et al, 2018 ; Han et al, 2019 ; Tejido-Rastrilla et al, 2019 ; Xie et al, 2019 ; Deng et al, 2020b ; Albashari et al, 2021 ). Deng ( Deng et al, 2020b ) developed a “PDA−Ag−PDA” sandwich structure on PEEK substrates via layer-by-layer process, which exhibited bacteria-triggered pH-responsive ion-releasing behavior, as well as biocompatibility and osteogenic activity.…”
Section: Pda-mediated Components For Multilayered Coatings On Biomate...mentioning
confidence: 99%
“…After evaluation, a synergistic enhancement of osteogenic gene expression could be observed, which is greater than scaffolds loaded with individual BMP-2 and VEGF. Besides, during fabrication of PDA-based multilayered coatings, other components can also be combined with VEGF and bFGF for extended multifunctionalization, like metallic ions and bioceramics ( Albashari et al, 2021 ; Li J. et al, 2021 ). Albashari et al ( Albashari et al, 2021 ) designed a bFGF cross-linked Ag coating via PDA and heparin intermediate layer on Ti substrates, which showed satisfying osteogenic differentiation, anti-inflammatory and antibacterial property.…”
Section: Pda-mediated Components For Multilayered Coatings On Biomate...mentioning
confidence: 99%